Phonon-assisted anti-Stokes excitation of the fluorescence of Mn²⁺ ions in the CsMnCl₃ ּ 2H₂O crystal - Eremenko, V.V.; Fomin, V.I.; Kurnosov, V.S. (Физика низких температур, 2000)
We demonstrate that anti-Stokes excitation of Mn²⁺ ions in the CsMnCl₃⋅2H₂O crystal can occur through multiphonon addition to the energy of the photons of exciting light. The deficit dE between the energy of the Mn²⁺  ⁴T₁ exciton and the photon energy of the He–Ne laser used as the source of illumination is compensated by simultaneous annihilation of several thermally activated lattice phonons. The absence of two-photon activation of the fluorescence was verified by measurement of the dependence of the fluorescence intensity on the intensity of the exciting light, which appears linear at a fixed energy mismatch dE.